Deep Web and Dark Web: similarities and dissiparities in the context of Information Science - Vignoli, Richele Grenge [UNESP]; Monteiro, Silvana Drumond (Pontificia Universidade Catolica Campinas, 2020)
In this article, we aim to demystify the Deep Web and the Dark Web, in addition to presenting the main similarities and disparities between them, essentially in regard to their: (1)Term; (2) Definition; (3) Metaphorical location in cyberspace through figures; (4) Types of contents; and (5) Ways of access. The research was documental and bibliographic, with searches in the Web of Science, Scopus Elsevier, Scientific Eletronic Library Online, Base de Dodos Referencial de Artigos de Periodicos em Ciencia da Informacao, Science Direct, Google Scholar, and various scientific journals. The main relationships (similar and dissimilar) between the. Deep Web and the Dark Web are presented in the article. However, new and necessary studies on the hidden and deep layers of the cyberspace should be carried out and disseminated in the field of Information Science.
Keywords: Cyberspace; Invisible Wep; Dark Web